1998
DOI: 10.1097/00000478-199812000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Atypical and Malignant Solitary Fibrous Tumors in Extrathoracic Locations

Abstract: Solitary fibrous tumor (SFT), first described as a pleural lesion, has been reported at numerous extrathoracic sites over the past 10 years. About 10% to 15% of intrathoracic SFTs are histologically or clinically malignant, but such cases have very rarely been described at other locations. Among 92 cases of extrathoracic SFT in our files, we identified 10 that either had recurred (2 cases) or had a least one atypical histologic feature (8 cases). The ten tumors occurred in five men and five women, 32 to 81 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
534
0
22

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 607 publications
(574 citation statements)
references
References 42 publications
18
534
0
22
Order By: Relevance
“…18 In another large study of 92 extrathoracic solitary fibrous tumors, 5 of 10 cases with atypical features metastasized and an additional 3 tumors locally recurred; clinical follow-up was not provided for the remaining 82 tumors. 11 Our findings of a poor 10-year disease-specific survival of 73% is likely due to referral bias at a major sarcoma treatment center with a population skewed toward more aggressive tumors. In fact, our rates are in keeping with those reported specifically for cases historically diagnosed as hemangiopericytoma and malignant solitary fibrous tumor.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…18 In another large study of 92 extrathoracic solitary fibrous tumors, 5 of 10 cases with atypical features metastasized and an additional 3 tumors locally recurred; clinical follow-up was not provided for the remaining 82 tumors. 11 Our findings of a poor 10-year disease-specific survival of 73% is likely due to referral bias at a major sarcoma treatment center with a population skewed toward more aggressive tumors. In fact, our rates are in keeping with those reported specifically for cases historically diagnosed as hemangiopericytoma and malignant solitary fibrous tumor.…”
Section: Discussionmentioning
confidence: 77%
“…McMaster et al found that B10% of metastases occurred after 5 event-free years, while Vallat-Decouvelaere et al found that 40% of metastases occurred after 5 years. 11,16 Consequently, studies with short followup may not accurately reflect metastatic potential of tumors with malignant histological features, 7 although even in studies with longer follow-up, tumors defined as malignant using historical criteria did not metastasize. 19 In our study, 50% of metastases occurred after 36 months, but could present up to 19 years after initial resection.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, malignant and metastatic SFTs have been reported to occur in extraoral sites. Vallat-Decouveleare et al [23] and Gold et al [25] found local recurrence in 4.3% and 6.7% and metastases in 5.4% and 5.3%, respectively. Sites of distant metastases were lung, liver, bones, mesentery, mediastinum and retro-peritoneum [7].…”
Section: Discussionmentioning
confidence: 94%
“…This tumor usually shows increased cellularity, at least focally moderate to marked cytological atypia, areas of necrosis, numerous mitoses (>4 mitoses/10 high-power fields) and/or infiltrative margins [2,19,23]. Malignant SFT exhibits histologic features resembling malignant FH, malignant hemangiopericytoma, or fibrosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…115,116 Tumor cells are typically positive for CD34 (80%-90%), CD99 (70%), BCL2 (30%), epithelial membrane antigen (30%), and actin (20%). [117][118][119][120][121][122][123] Desmin, cytokeratin, and S100 are usually absent. 117 Recently, NAB2/STAT6 was identified in solitary fibrous tumors, strongly suggesting that this type of tumor is a translocation-associated neoplasm and that STAT6 immunostain is a sensitive and specific marker for solitary fibrous tumor.…”
Section: Solitary Fibrous Tumor/hemangiopericytomamentioning
confidence: 99%